Evaluación objetiva y subjetiva de parámetros de audio relacionados con la calidad en producciones musicales finalizadas - Obregón Gaviria, Daniel (Ingenierias, 2017)
The main purpose of the following work is to evaluate in an objective and subjective manner, audio parameters in finalized musical productions, which can be useful to determine their relationship with the perceived audio quality, taking into account audio attributes such as dynamic range, stereo image, and frequency content. To achieve this, algorithms were coded in the software MATLAB, to evaluate the following three specific parameters: IBR (Inter-Band Relationship), cross correlation, and harsh energy. Hearing tests were also designed in order to evaluate the same parameters in a subjective manner, to establish if there is an existing relationship between these parameters and the perception of audio quality.